Unlock Your Time: Pelatihan Peningkatan Manajemen Waktu - Ramadhani, Alvina; Syifa, Aulia; Sholehah, Esnita; Zahra Amellia, Nabilla; Asri Kamila, Syifa; Putri Agustina , Tsaniya (E-Coops-Day, 2025)
“Unlock Your Time: Time Management Improvement Training” aims to enhance students' skills in organizing and optimizing their time effectively. The primary focus of this training is to provide an understanding of the importance of time management through the Experiential Learning approach. This training is motivated by the challenges students face in completing academic tasks, participating in organizational activities, and maintaining life balance. The training phases include preparation, organization, and implementation, consisting of theory and practice sessions, including simulations, reflections, and group discussions. The training was attended by students from various programs and involved experienced facilitators. The results indicate an improvement in participants' understanding and ability to prioritize tasks using the Eisenhower Matrix and manage daily schedules through Google Calendar. In conclusion, this training successfully enhanced students' time management skills, as measured through practical evaluations and end-of-session reflections.